The Effects of Traditional and Digital Books on Early Literacy Skills in Preschoolers - Pearce, Rachel (East Carolina University, 2017)
Literacy is a skill that develops even before a child begins attending school. Traditionally, this exposure to literacy has relied solely on print books. However, this literacy exposure has shifted to include different forms of media, including e-books. The participants of this study included 19 3 and 4-year-old children from two different preschools in Greenville, NC. Pre-experimentally, speech, language, and hearing screenings were completed followed by the administration of The Test of Preschool Early Literacy (Lonigan, Wagner, Torgesen, & Rashotte, 2007). Experimentally, Dr. Seuss’s ABC book was read with each child in two different formats (traditional paper book and an interactive, electronic book on an iPad). After each book reading, the child was assessed on measures of letter naming, letter recognition, sound-symbol relationships, and sound/picture association. Accuracy for each measure was determined for each book type and compared as a function of book type, age, and gender. Overall, the mean accuracies for the traditional book were higher when compared to the e-book for each experimental task; however, only two of these differences were found to be statistically significant. The difference between book types for overall accuracy was found to be statistically significant, as well as for the sound-symbol relationship task. The sound-symbol knowledge accuracy was found to be higher for the traditional book (56.58%), as compared to the eBook (35.53%). The overall accuracy was found to be higher for the traditional book (60.94%), as compared to the eBook (48.75%). These results suggest that while the children were more engaged during the e-book reading, they were focused on the information unrelated to the experimental tasks, including sound-symbol relationships.
Keywords: literacy, language, preschool